Kajian Yuridis Pemberhentian Tenaga Kontrak Daerah secara Sepihak oleh Bupati Manggarai Barat melalui Surat Pemberitahuan Nomor BKPPD 870/536/XII/2021 - Marianus Fenansio Kolo; Darius Mauritsius; Chatryen Megawati Dju Bire (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze juridically the unilateral termination of regional contract employees by the Regent of West Manggarai through Notification Letter Number BKPPD.870/536/XII/2021, as well as to examine the termination process and the fulfillment of the affected employees’ rights. The research problems focus on how the termination process was carried out and how the rights of the contract employees were fulfilled following the unilateral termination. The research employs an empirical legal method with a descriptive qualitative approach. Data were obtained through interviews with dismissed contract employees and local government officials, and were supported by secondary data derived from legislation and legal literature. The results show that the termination process of regional contract employees in West Manggarai Regency did not comply with applicable legal procedures, particularly the provisions of Law Number 13 of 2003 on Manpower. The termination was conducted without bipartite negotiations or the mechanism for industrial relations dispute settlement, thereby constituting a procedural defect. Furthermore, the fulfillment of employees’ rights was not carried out optimally, as most contract employees did not receive compensation despite the remaining period of their employment contracts. Accordingly, improvements are required in local government policy mechanisms regarding the management of contract employees to ensure alignment with the principles of justice, legal certainty, and the protection of workers’ rights.